Barbárie e Civilização: imagens dos índios nos viajantes no Rio de Janeiro oitocentista - Roberta Ketllen Souza Duarte (Universidade Federal do Amazonas, 2017)
Over the nineteenth century, became common the presence of foreign travelers in the city of Rio de Janeiro. The applicant therefore reports always attracted the attention of historians. In 1988, José Freire stated that the regional historiography had silenced the indigenous presence in the nineteenth century, especially in Rio de Janeiro and drew attention to the documents available in the collections of Rio de Janeiro that attested to the indigenous presence both in the province and in the cities, going against a historiography that silenced them. One of these documents highlighted by the author are the travel accounts. For the research were selected reports from the English merchant John Luccock and French journalist Charles Ribeyrolles, who visited Brazil in the first decades and in the second half of the nineteenth century, respectively. Two questions are central to the research: the first concerns the scarce historiography about the indigenous presence in the nineteenth century Rio de Janeiro proposing to discuss the invisibility of the Indians. The second is related to the fact that the accounts left by travelers were important in the construction of certain images about the Indians. Such images implied in the use of classificatory categories that passed through concepts such as "barbarism" and "civilization." We learn such classificatory categories used by these authors seeking to associate them to a set of existing ideas about the ideal of civilization to the indigenous peoples of Brazil.